2019
DOI: 10.1039/c8cp05983g
|View full text |Cite
|
Sign up to set email alerts
|

An in situ FTIR study of the plasma- and thermally-driven reaction of isopropyl alcohol at CeO2: evidence for a loose transition state involving Ce3+?

Abstract: This paper reports on the thermally-driven and non-thermal plasma-driven reaction of IsoPropyl Alcohol (IPA) on ceria (CeO2) with the aim to investigate the differences between plasma catalytic interactions and the analogous thermal reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The slow progress in mechanism exploration is partially due to the interference of microdischarges, electrical creepage and arcing, and electromagnetic noise, which make it difficult to apply the well-established characterization methods from thermocatalysis to investigate plasma reactions. Recently, a few studies have employed operando IR spectroscopy to study catalyst surfaces during plasma-catalysis processes. , Implementation of these characterization methods and other in situ techniques, coupled with computational analysis of plasma-activated CO 2 + CH 4 conversion, may reveal the mechanisms governing plasma–catalyst interactions and guide the development of oxygenate-selective catalysts.…”
Section: Summary and Perspective On Challengesmentioning
confidence: 99%
“…The slow progress in mechanism exploration is partially due to the interference of microdischarges, electrical creepage and arcing, and electromagnetic noise, which make it difficult to apply the well-established characterization methods from thermocatalysis to investigate plasma reactions. Recently, a few studies have employed operando IR spectroscopy to study catalyst surfaces during plasma-catalysis processes. , Implementation of these characterization methods and other in situ techniques, coupled with computational analysis of plasma-activated CO 2 + CH 4 conversion, may reveal the mechanisms governing plasma–catalyst interactions and guide the development of oxygenate-selective catalysts.…”
Section: Summary and Perspective On Challengesmentioning
confidence: 99%
“…What is more, this same study demonstrated that when using Ag nanoparticles supported on catalysts, they served as oxygen reservoirs. As for VOC removal with non-thermal plasma-assisted catalysis, isopropanol [23,24], toluene [24,25] and acetone removal [26] have been studied using an FTIR in-situ technique. This approach allowed the identification of reaction intermediates, and the following of the evolution of secondary compounds arising from the VOC oxidation.…”
Section: Introductionmentioning
confidence: 99%